Improving fit of bicycle helmet liners using 3D anthropometric data - Skals, Sebastian; Ellena, Thierry; Subic, Aleksandar; Mustafa, Helmy; Toh, Yen Pang (Elsevier, 2016)
3D anthropometry has provided much-needed information about the size and shape of the head, which can be used to improve the fit of protective helmets. In this study, a new 3D head scan sizing method was implemented in a reverse engineering approach for bicycle helmet liner dimensioning. The inside liner of a commercially available helmet was modified to improve the fit for a selected size group of 30 participants. The fit of the standard and new liner were assessed and compared, using the Helmet Fit Index (HFI). The HFI scores showed a significant improvement of overall fit (Difference: 11.32 ± 7.82 (μ ± SD), p < 0.0005) and for each of five defined regions of the liner inside surface. The presented methodology for dimensioning helmet liners based on 3D anthropometry proved effective, resulting in improved fit for the end users.